Derivations of the Algebra of Sections of Superalgebra Bundles - N. Elyasi (Journal of Sciences, Islamic Republic of Iran)
In this paper we review the concepts of the superalgebra, superderivation and some properties of them. We will define algebraic and differential superderivations on a superalgebra and will prove some theorems about them, Then we consider a superalgebra bundle, that is an algebra bundle which its fibers are superalgebras and then characterize the superderivations of the algebra of sections of that bundle.